(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Mushrooms are ironic in nutrimental resources and have converted into one of the common foods in the previous twenty years globally. The types of edible mushrooms are button, milky and oyster mushrooms. The research aimed at value addition of Oyster mushrooms by rising on paddy substrate complemented with two concentrations of four different medicinal plants. The plant parts selected were flowers of Butea monosperma, leaves of Moringa olifera, bark of Cinnamonom zeylianicum, fruits of Corindraum sativum at 5% and 10% concentration. Different species of oyster mushrooms are available. In the present study Pleurotus florida was selected for value addition. Maximum mycelium running rate was detected in Cinnamon bark (5%) and paddy straw (95%) accompanied group and lowermost running rate of mycelium was observed in Moringa leaf (5%) and paddy straw (95%). The primordial arrival was fast with Cinnamon bark (5%) supplemented group and slowest in Moringa leaf (5%) supplemented group. The mushrooms grownup on Coriander fruit (5%) produced more but the growth was slow. Mushrooms supplemented with Butea flower (5%) exhibited slow growth and yield was next to coriander fruit supplemented mushrooms. The produced mushrooms were subjected to physical evaluation, preliminary phytochemical testing and also tested for estimation of total flavonoids, total phenols, total tannins and total cinnamaldehyde contents. Value addition of Oyster mushrooms was successful with cinnamon bark as cinnamaldehyde was noticed in the Cinnamon bark supplemented group, and also with Moringa leaves as flavonoids was observed in more concentration in Moringa leaf supplemented mushroom group.